DECOLOURIZATION OF TRIPHENYLMETHANE DYES AND DYE INDUSTRY EFFLUENT BY STAPHYLOCOCCUS AUREUS ISOLATED FROM DYE CONTAMINATED SITE - Sandhiya, R.; Begum, K. Sumaiya; Charumathi, D. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objectives of the present study were a) to isolate and screen bacteria for dye removal from synthetic solution b) to optimize various variables such as pH, static/shaking and initial dye concentration on degradation of triphenyl methane dyes namely basic violet 3 and basic green 4 by isolated Staphylococcus aureus c) to analyse enzymes involved in the biodegradation of triphenylmethane dyes d) to treat real leather dyeing wastewater with newly isolated strain of Staphylococcus aureus e) to characterize untreated and treated leather dyeing wastewater f) to study the effects of real and treated effluent on plants and Rhizobium. Methods: Isolation of bacteria from sludge was carried out by spread plate method and the bacteria was identified by morphological and biochemical characterization. The isolated bacterium was screened for dye decolorization potential of triphenylmethane dyes basic violet 3 and basic green 4 The effects of parameters were studied by varying pH (from 3 to 9), temperature (from 15-45 Â°C), and initial dye concentration (from 10-500 mg/l). The enzyme involved in biodegradation was studied in intracellular extract. Real leather dyeing wastewater was treated with the bacteria and characterized. The treated wastewater was tested on plants and Rhizobium for toxicity. Results: Dye decolorization potential of bacteria Staphylococcus aureus isolated from wastewater for leather dyes basic violet 3 and basic green 4 were evaluated. Dye decolorization using bacteria was found to be dependent on physicochemical parameters (shaking, pH and initial dye concentration). Enzymes NADH-DCIP reductase and MG reductase were found to play dominant role during biodegradation of synthetic dyes. Application oriented studies using growing bacteria in pure cultures were carried out with leather dyeing wastewater collected from DKS prime tanners. Analysis of raw leather dyeing wastewater showed high pollution load in terms of color, Total solids, Total suspended solids, Total dissolved solids and Biological oxygen demand whereas the leather dyeing wastewater treated with pure culture of Staphylococcus aureus showed considerable decrease in Total solids, Total suspended solids, Total dissolved solids and Biological oxygen demand values which were within the permissible limits. Phytotoxicity and microbial toxicity studies confirmed the non-toxic nature of treated leather dyeing wastewater. Conclusion: Our study proved that Staphylococcus aureus can serve as a potential remediation agent for the treatment of leather dyeing wastewater.